New discovery of prehistoric archaeological remnants in volcanic caves in K’Rongno, Dak Nong province - Phuc*, La The; Su, Nguyen Khac; Duc, Vu Tien; Tuat, Luong Thi; Toan, Phan Thanh; Tung, Nguyen Thanh; Minh, Nguyen Trung (Vietnam Journal of Earth Sciences, 2017)
The Krongno Volcanic Geopark in Dak Nong province with a unique and largest volcanic cave system in SE Asia discovered in 2007 occupies an area about 2,000 km2 in the Krong No, Cu Jut and Dak Mil districts and several neighboring communes in the Dak Song and Dak Glong districts. In 2016, Vietnamese archaeologists discovered a number of archaeological sites in hilly, farmland and riverine areas in the Krong-No Volcanic Geopark; however, none had been found in the volcanic caves. During the late December 2016 - early January 2017 field trip, a survey team led by Vietnam National Museum of Nature, VAST, discovered a series of archaeological sites and relics with a relatively high density in volcanic caves in the Krongno Volcanic Geopark. The discovered archaeological remnants include (1) stone materials and tools such as dish-shaped tools, short axes, blade-ground short axes, oval axes and blade-ground oval axes; flake tools, stone flakes, stone slabs; anvils, graters, pestles, etc., hand-fitting sharp quartzite stones and pieces of loess; (2) pottery, containing various ceramic tools with different thicknesses, mostly fired at low temperature, crumbly, made of fine sandy loam, hand-kneaded, simple forms, mainly pots and containers having relatively sharp sculptings of varied patterns on the pottery shards such as dot-dash, dotted line, dashed line, twisted rope, etc.; (3) animal and teeth bones, including fragments of animal bone, or bones of prehistoric human (?). The bones are mostly decayed and fragile when dry; the hollow portions of bones are filled with porous clay slurry. In addition to the bone fragments, there are cheek teeth of animals some are fossilized. Preliminary determination suggested the teeth are of herbivores. Most of the archaeological artifacts were found in caves with flat floors, having mouths facing east, southeast or south heading to relatively wide areas to absorb the light, close to water sources and convenient to commute. These are the first prehistoric archaeological findings in volcanic caves in Vietnam, which will be studied in more detail by Vietnam National Museum of Nature, VAST, and other authorized agencies to highlight a new type of settlement, a new adaptive trend of prehistoric dwellers in the Central Highlands and to open a new archaeological study in the volcanic caves in Vietnam and Southeast Asia. References La The Phuc, Hiroshi Tachihara, Tsutomu Honda, Truong Quang Quy, Luong Thi Tuat, 2015. The geological heritage of unique volcanic cave in Dak Nong has been discovered and established the record. Journal of Geology, Series A, 349, 1 - 2/2015, 28-38. Le Hai Dang, et al. (2013). Preliminary results of the second excavation in the Thon Tam archaeological site (Dak Nong), in “New discoveries in archeology in 2013”, 03-105. Nguyen Gia Doi, Le Hai Dang, et al., 2006. Discovery of archaeological site of stone tool workshop in Thon Tam (Dak Nong). In “New discoveries in archeology in 2006”. Social Sciences Publishing House. Nguyen Duc Thang (Chief Author), 1989. Geology and Minerals in Ben Khe - Dong Nai map sheet group, on the scale 1: 200,000. General Department of Geology and Minerals of Vietnam. Hanoi. Nguyen Khac Su (Chief Author), 2004. Prehistoric archaeology in Dak Lak. Social Sciences Publishing House, Hanoi. Nguyen Khac Su, 2007. Prehistoric archaeology in the Central Highlands. Education Publishing House, Hanoi. Nguyen Van Tran, Hoang Thu Nguyen, 2011. The discovery of stone axes in Dak Song (Dak Nong). In “New discoveries in archeology in 2009’’. Social Sciences Publishing House, 96-97. Truong Quang Quang, et al., 2011. The newly discovered stone hoes in Cu Jut (Dak Nong). In “New discoveries in archeology in 2010’’. Social Sciences Publishing House, 97-98. UNESCO Division of Ecological and Earth Sciences, 2009. Global Geopark Network. Vu Tien Duc, 2015. The report for scientific project at Institute of Social Sciences of Central Highlands “Investigation of prehistoric archaeological remains in Dak Wil, Cu Jut, Dak Nong’’.